A Reliable Method for Prediction of the Condensed Phase Enthalpy of Formation of High Nitrogen Content Materials through their Gas Phase Information. Issue 16 (10th October 2016) - Jafari, Mohammad; Keshavarz, Mohammad Hossein; Noorbala, Mohammad Reza; Kamalvand, Mohammad
Abstract: The condensed phase standard enthalpy of formation of energetic materials plays important role in assessment of their detonation and combustion performance. High nitrogen content materials can be considered as high‐performance energetic materials because they have relatively high positive values of the condensed phase heat of formation. Two new models were presented for prediction of the condensed phase standard enthalpy of formation for compounds containing more than 50 % of nitrogen. The new models need the calculated values of gas phase standard enthalpies of formation, which were calculated on the basis of B3LYP/6‐31G* method or the semiempirical PM6 method. Moreover, the effects of some structural parameters, such as hydrogen bonding, were considered in order to increase the accuracy of models. Reliability of the new models has been confirmed as compared with several of the best and new available methods. Abstract : High nitrogen content molecules can be classified as a new generation of high energy density materials. Different derivatives of five or six membered nitrogen‐containing rings such as triazoles, tetrazoles, furazans, triazines, tetrazines, and some of the nitrogen‐containing chains fall in this category. Their detonation performance depends on their densities and heats of formation. In the current work, two reliable and accurate models have been introduced for predicting the condensed phase heats of formation of high nitrogen content materials.